Ouvidorias públicas: por uma sociedade democrática e cidadã - Carneiro, Tony Geraldo (2014)
Lined in the genesis of national political organization, seeks to reduce the complexity of social and political organization prevailing system, consolidating on key historical events, responsible for building the basis of citizenship and consequent awareness of the need for interaction between rulers and ruled, thus was born the institute of ombudsman public in order to fill the gap of communication and society participation in governance state. This work, in addition to addressing the roots of generating political support base of the institute of ombudsman, brings to fore the changing needs of the institute in national and international bias, limiting the playing field, major public and private actions that corroborated and corroborate the organization and structuring of public sector ombudsmen. Concomitantly, entered to the world of e-governance in favor of a new relational format, improving the emancipatory process of transparency, participation and democratization National. We highlight special attention to the model used in the Federal Executive, the body that is driving the Ombudsman General of the Union, as the work under the Ministry of Agriculture, Livestock and Supply argued that motivated the main arguments (theoretical and empirical) of this research.